FREQUENCY OF REFRACTIVE ERROR AND AMBLYOPIA IN STRABISMUS IN PEDIATRIC AGE GROUP - Noureen Malik; Hannan Masud; Imran Basit; Palwasha Noor (Pakistan Armed Forces Medical Journal, 2021)
Objective: To see the frequency and compare the type of refractive error and strabismus in amblyopic versus non amblyopic children.